The tailored traits of reclaimed asphalt pavement incorporating maltene: performance analyses - Putra Jaya, Ramadhansyah; Zaid Hazim, Al-Saffar; Haryati, Yaacob; Mohd Khairul Idham, Mohd Satar (Taylor & Francis Group, 2020)
Environmental issues and fluctuations in the price of asphalt binders have increased the demand in usage of reclaimed asphalt pavement (RAP) material for asphalt mixtures. The RAP binder, nevertheless, is often highly aged and has several drawbacks, for instance, low cracking resistance, low workability, and low fatigue in the resulting mixtures. These issues can be resolved by using rejuvenators. As such, this research work assessed the engineering properties of reclaimed hot-mix asphalt (HMA) mixture rejuvenated by maltene-derived asphalt. The tests examined Marshall properties, moisture damage, resilient modulus (MR), dynamic creep, Cantabro loss, and rutting resistance, including the stripping and coating tests. The results showed that maltene had been effective in mitigating the aging effect of RAP asphalt, while the rejuvenated mixture exhibited considerable enhancement, especially when compared to the virgin and RAP mixtures without maltene. A simple cost analysis revealed that maltene was cost-effective as it compensated for the adverse effects of RAP, hence can be used to raise the content of RAP in asphalt mixture.